2022
DOI: 10.3389/fimmu.2022.841254
|View full text |Cite
|
Sign up to set email alerts
|

Gpr174 Knockout Alleviates DSS-Induced Colitis via Regulating the Immune Function of Dendritic Cells

Abstract: BackgroundDysfunction of the immune system would disturb the intestinal homeostasis and lead to inflammatory bowel disease (IBD). Dendritic cells (DCs) help maintain intestinal homeostasis and immediately respond to pathogens or injuries once the mucosa barriers are destroyed during IBD. G protein-coupled receptors(GPR)174 is an essential regulator of immunity that is widely expressed in most immune cells, including DCs. However, the role of GPR174 in regulating the immune function of DC in colitis has not bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…These excessive ROS can act as upstream stimuli to evoke aberrant activation of the intestinal immune system, causing damage to the intestinal mucosal barrier, including a decrease in mucous secretion, antimicrobial peptide secretion, and the destruction of tight junctions [ 15 ]. Importantly, radical immune cells activate inflammatory signaling pathways such as NF-κB, JAK/STAT, and MAPK signaling pathways [ 16 , 17 , 18 ], promote the release of proinflammatory factors (e.g., TNF-α, IL-6, and IL-1β) and oxidases (e.g., iNOS, COX-2, and NOX [ 19 , 20 ]), and further increase the level of oxidative stress in the intestinal tract [ 21 ], which will remold the gut microbiota and form a loop of oxidative stress–ROS–inflammation–ROS–oxidative stress ( Figure 1 ). Accordingly, such a loop can be used as a potential therapeutic target to avoid the occurrence and progression of intestinal inflammation by alleviating oxidative stress in the intestine and reducing the stimulation of gut microbiota and immune cells by ROS, thereby recovering the intestinal mucosal barrier.…”
Section: Introductionmentioning
confidence: 99%
“…These excessive ROS can act as upstream stimuli to evoke aberrant activation of the intestinal immune system, causing damage to the intestinal mucosal barrier, including a decrease in mucous secretion, antimicrobial peptide secretion, and the destruction of tight junctions [ 15 ]. Importantly, radical immune cells activate inflammatory signaling pathways such as NF-κB, JAK/STAT, and MAPK signaling pathways [ 16 , 17 , 18 ], promote the release of proinflammatory factors (e.g., TNF-α, IL-6, and IL-1β) and oxidases (e.g., iNOS, COX-2, and NOX [ 19 , 20 ]), and further increase the level of oxidative stress in the intestinal tract [ 21 ], which will remold the gut microbiota and form a loop of oxidative stress–ROS–inflammation–ROS–oxidative stress ( Figure 1 ). Accordingly, such a loop can be used as a potential therapeutic target to avoid the occurrence and progression of intestinal inflammation by alleviating oxidative stress in the intestine and reducing the stimulation of gut microbiota and immune cells by ROS, thereby recovering the intestinal mucosal barrier.…”
Section: Introductionmentioning
confidence: 99%
“…The GSEA enrichment analysis showed that gene sets grouped according to IGSF6 expression were mainly enriched in cytokine-receptor interaction and intercellular interaction. It has been well established that antigen peptide-MHCII complex presented by macrophages and DCs is essential for the activation of Th1 cells [27][28][29][30]. Previous studies have also proposed that IGSF6 may be closely related to antigen uptake, or the recirculation of DCs [13].…”
Section: Discussionmentioning
confidence: 99%
“…MC group mice continuously drank 3% DSS solution for 16 days based on the method described previously with minor modifications (Wang et al, 2020; Wei et al, 2022; Zhou et al, 2022). Except for mice in the NC group that were provided pure water by gavage, the SASP and SchA groups were administered their respective drugs daily.…”
Section: Methodsmentioning
confidence: 99%